EFFECTS OF REWARD BUNDLING ON MALE RATS' PREFERENCE FOR LARGER–LATER FOOD REWARDS1. Issue 2 (14th January 2013) - Stein, Jeffrey S.; Smits, Rochelle R.; Johnson, Patrick S.; Liston, Kennan J.; Madden, Gregory J.
Abstract In both humans and nonhumans, prior research demonstrates increased preference for larger‐later over smaller‐sooner rewards when rewards are bundled together in a series (i.e., when an operant choice produces multiple discrete reward deliveries, as opposed to only a single delivery). These findings can be predicted using a traditional hyperbolic delay‐discounting model. The present study was designed to examine the parametric effects of the size of the reward bundle on larger‐later reward preference in male rats. During a reward‐bundling phase, rats were exposed to bundle‐sizes of either 1 (i.e., no bundling), 3, or 9 rewards. Rats in the Bundle‐size 9 group showed significantly greater larger‐later reward preference across a range of delays (0‐17.5 s) than rats in any other group, but no other significant differences in choice were observed between groups. In addition, when choice for unbundled rewards was assessed following the reward‐bundling phase, rats in the Bundle‐size 9 group showed a significant increase in larger‐later reward preference (compared to a pre‐test). Obtained data from the reward‐bundling phase are compared to model‐predicted data, and potential mechanisms of the observed increase in self‐control for unbundled rewards are discussed.